Technology usage and organizational performance in the medium sized manufacturing enterprises: does network competence matter? - Ezuma, Kingsley Eze; Hamzah, Siti Raba’ah; Ismail, Ismi Arif; Abdullah, Abdul Lateef Krauss (Human Resource Management Academic Research Society, 2019)
The main objective of this paper is to determine whether network competence matters in the relationship between technology usage and organizational performance of medium-sized manufacturing enterprises in the state of Lagos, Nigeria. This study examines the conceptual relationships in the Nigerian context. The data for the study were based on the responses to structured questionnaires that were completed by 245 owners/managers of medium sized manufacturing enterprises. The Statistical Package for Social Sciences (SPSS) was used for descriptive analysis (mean values, frequencies and percentages), and Structural Equation Modelling (SEM) using AMOS was employed for inferential statistics. Furthermore, the mediating effect was examined using bootstrapping analysis. HRD indicators for performance (namely effectiveness, efficiency, development, satisfaction, innovation, and quality) were used to measure organizational performance.The findings showed that the integration of network competence practices and technology usage did translate to improved organizational performance. Network competence served to promote a degree of trust within and outside interdependent firms. Furthermore, practices related to development of the individual’s skills in technology usage should be adopted to improve organizational performance. The findings indicated that network competence partially mediated the relationship between technology usage and organizational performance of medium-sized manufacturing enterprises. The findings would help Nigerian owners/managers involved in medium-sized manufacturing enterprises adopt the right human resource development practices, including the development of technology usage skills and network competence capabilities.